Behavioral and Morphological Adaptations of Tortoise Tick Hyalomma aegyptium to Testudo graeca: Evidence for Complex Evolutionary History - Sirri Kar; Baris Donmez; Bugrahan Regaip Kilinc; Zafer Sakaci; Sengul Talay; Dennis Bente; Agustin Estrada‐Peña (Ecology and Evolution)
ABSTRACT In vector arthropods, the host relationship plays a central role in population dynamics and is crucial for determining the current and future course of vector ecology and the eco‐epidemiology of vector‐borne diseases, particularly under the influence of climate and environmental changes. However, since this relationship is driven by complex ecological cascades, accurately characterizing its attributes, particularly in a cause‐and‐effect context, remains challenging, leaving substantial gaps in understanding. In this study, we examined the infestation characteristics of the tick species Hyalomma aegyptium on its specific host, the spur‐thighed tortoise Testudo graeca, to investigate the principles of behavioral and morphological adaptation and its ecological consequences. A field study was conducted in 2021 and 2022 in Turkish Thrace to obtain phenology‐based data under natural conditions. During the survey, a total of 20,933 ticks were examined on 878 tortoises, with 96.1% prevalence, 24.8 ± 30.6 intensity, and 23.8 abundance. The analyses revealed that all infestation traits were directly influenced by the tick's developmental stage, sex, and morphological characteristics, as well as the tortoise's sex, size, behavioral traits, and phenological patterns. The comprehensive evaluation of behavioral and morphological traits demonstrated that several features and behaviors in H. aegyptium are highly specialized to permit T. graeca infestation. All these traits seem evolutionarily driven to shield the tick from environmental and feeding‐related challenges while minimizing the infestation's life‐threatening pressure on the host. Although these remarkable adaptation characteristics suggest a deep‐rooted coevolutionary background, some critical discrepancies in the fundamentals of host–parasite interactions make it more plausible that the primary speciation process of H. aegyptium had already occurred in an extinct giant tortoise species before its adaptation to the genus Testudo.